2021
DOI: 10.3390/jcm10173779
|View full text |Cite
|
Sign up to set email alerts
|

BK Virus and Cytomegalovirus Coinfections in Kidney Transplantation and Their Impact on Allograft Loss

Abstract: We aimed to ascertain the interaction and effects of combined reactivations of BK virus and cytomegalovirus on kidney graft function. All consecutive kidney transplant recipients (KTR) between 2003 and 2016 were included. Of 1976 patients who received a kidney transplant, 23 (1.2%) presented BKV-associated nephropathy (BKVAN). Factors independently associated with BKVAN were diabetes mellitus (odds ratios (OR) 3.895%, confidence intervals (CI) (1.4–10.5)), acute allograft rejection (OR 2.8 95%, CI (1.1–7.6)) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Our finding that CMV could be related to urological problems is instead uncommon: to the best of our knowledge, this observation was only recently suggested by Herrera et al [ 40 ]. In that study, the authors noted increased nephrostomy requirements in recipients with CMV, leading to their speculation that the need for nephrostomy is more common in patients with post-transplant complications with a heightened state of immunosuppression.…”
Section: Discussionsupporting
confidence: 49%
“…Our finding that CMV could be related to urological problems is instead uncommon: to the best of our knowledge, this observation was only recently suggested by Herrera et al [ 40 ]. In that study, the authors noted increased nephrostomy requirements in recipients with CMV, leading to their speculation that the need for nephrostomy is more common in patients with post-transplant complications with a heightened state of immunosuppression.…”
Section: Discussionsupporting
confidence: 49%
“…Post-transplant pyelonephritis is the most common bacterial infection in kidney transplant recipients [ 13 ] and is associated with an increased risk of graft loss and death [ 14 ]. CMV and BK virus infections are the major infection complications in renal transplant recipients [ 15 ]. Viral infections are biomarkers of excessive immunosuppression, and monitoring for reactivation of these viral infections should be routine.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the TAC trough level was high when CMV colitis occurred, which may suggest the relationship between blood levels of immunosuppressants and CMV colitis. Patients with CMV reactivation should be actively screened for the BK virus [ 15 ]. In this case, we screened for and diagnosed the patient with BK virus infection and reduced immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…The mean time of BKVN diagnosis in our patients was observed to be 6.8 ± 2.4 months after transplantation, while the graft loss rate was 12.5%. In different studies, graft loss rates have been reported as 40-80% [7][8][9][10][11][12][13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%